Activity Budgets of Impala (Aepyceros melampus) in Closed Environments: The Mukuvisi Woodland Experience, Zimbabwe. (30th May 2013) - Victor Kurauwone, Muposhi; Justice, Muvengwi; Beven, Utete; Olga, Kupika; Simon, Chiutsi; Tawanda, Tarakini
Abstract : Activity pattern plasticity in ungulates serves as an evolutionary adaptation to optimize fitness in inconsistent environments. Given that time is a limited and valuable resource for foraging wildlife species, provisioning and attraction may affect the activity pattern plasticity and reduce complexities of time partitioning for different activities by impala in closed environments. We assessed activity budgets of free-ranging impala social groups in a closed environment. Social group type had an influence on the activity budgets of impala except for foraging and moving activity states. Both the harem and bachelor groups spent more than 30% of their daily time foraging. Bachelor groups spent more time exhibiting vigilance tendencies than the harem groups. Season influenced the activity budgets of social groups other than vigilance and foraging activity states. Foraging time was highly correlated with vigilance, resting, and grooming. We concluded that provisioning and attraction may have reduced the influence of seasonality on the proportion of time spent on different activity states by impala social groups. There is a need to establish long-term socioecological, physiological, and reproductive consequences of provisioning and habituation on impala under closed environments.